Adoption of Digital Agro-Advisory Services Among Smallholder Farmers: Patterns of the Innovation-Decision Process - Vaidya, Bristi; Rana, Hritika; Sharma, Sagar Raj (Bodhi: An Interdisciplinary Journal, 2023)
Various digital agricultural advisory services have been developed to effectively exchange agriculture related information, skill and knowledge with the farmers. However, innovation and readiness of such technology does not guarantee that it will be adopted by the farmers. This study focuses on understanding farmers’ adoption of digital agroand non-adoption. A mixed-method research was conducted with 50 farmers of Kageshwori Manohara Municipality of Bagmati province, Nepal, who were also the users of mobile-based agriculture application, innovation theory was used as an analytical lens for data interpretation. terms of their adoption decision i.e., passive rejecters, active rejecters as digital literacy, farmer’s agricultural needs, communication channel, farmer’s social network, socio-economic and household dynamics and technological cluster. The study further argues that such innovations need to incorporate information that not just aligns with the needs of any farmers but should also be based on the local context.